Nailflow Application Interface Design Using Design Thinking Methods to Support Nail Ordering Efficiency - Nining Ariati; Veby Nazila Putri; Jessica Oktaviani; Ina Diana; Della Novita; M Aidil Irawan (Manunggal Halim Jaya, 2026)
The development of information technology requires the industry to transform into a digital system to improve efficiency and service. CV. Tjahaya Logam, as a nail manufacturing company, still uses a manual ordering system that has the potential to cause recording errors and late confirmation. To overcome these problems, the NailFlow application interface was designed using the Design Thinking method with five main stages: Empathize, Define, Ideate, Prototype, and Test. The purpose of this design is to produce a user interface (UI) and user experience (UX) design that is intuitive, efficient, and meets the needs of customers and company admins. The design results in a prototype application with key features such as digital ordering, real-time order tracking, and stock management. Testing using the Black Box Testing method shows that all interface elements function as expected. With this interface design, it is hoped that NailFlow can improve the efficiency of the ordering process, reduce errors, and provide a better service experience for CV. Tjahaya Logam customers.